Study of the Behavior of Some Spring Barley Lines with Two Rows Created at A.R.D.S Turda Regarding Production Capacity and Quality - Ioana PORUMB; Florin RUSSU (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Agriculture, 2017)
The spring barley is a variety of a superior quality for brewing compared with the feed barley due to several reasons. Research was conducted in the field of breeding of spring barley with two rows, within ARDS Turda, during 2013-2015. The trials were comparatively developed, and included 25 variants. The biological material was represented by four  autochthonous genotypes: Turdeana, Daciana Romaniţa (A.R.D.S. Turda), and Adina (A.R.D.S. Suceava). The spring barley lines created by the S.C.D.A. Turda, meet the requirements of the beer industry in terms of protein content, starch, M.M.B. and germination energy.